The Addition of Indian Almond Leaf Extract to Caudal Epididymal Plasma Diluents Effectively Maintains The Quality of Frozen Simmental Bull Sperm - Fahrezi, Muhammad Thoriq; Nur Ducha; Rofiqul A'la (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2026)
The decline in sperm quality during the freezing process is generally attributed to cold shock and the accumulation of Reactive Oxygen Species (ROS), which damage cell membranes, proteins and DNA, thereby reducing sperm motility, viability and potential fertility. Natural antioxidants such as Indian almond or Ketapang leaf extract (Terminalia catappa) have the potential to neutralize free radicals due to their flavonoid and phenolic content. This study was aimed to evaluate the effect of adding Indian almond or Ketapang leaf extract to Cauda Epididymis Plasma (CEP) diluent on the quality of frozen semen from Simmental bull. The study employed a completely randomized design with four Indian almond or Ketapang leaf extract doses (0, 0.013, 0.025, and 0.038 mg/mL) and six replicates. Sperm quality evaluation included motility, viability and plasma membrane integrity. Data were analyzed using Analysis of variance and a significantly difference between the treatments, was continued with the Duncan's multiple range test. Results showed that the addition of 0.038 mg/m extract yielded the highest values, namely sperm motility of 56.7 ± 2.9% (equilibrated) and 43.3 ± 2.9% (post-thawed), viability of 87.3 ± 1.2% (equilibrated) and 79 ± 0% (post-thawed) and membrane integrity of 84.7 ± 0.6% (equilibrated) and 79.7 ± 1.2% (post-thawed). These differences were significant compared to other treatments (P<0.05). This study concludes that a dose of 0.038 mg/mL of Indian almond or Ketapang leaf extract is effective in maintaining spermatozoa quality during freezing through its antioxidant activity, which prevents oxidative damage. This finding is potentially applicable in reproductive technology to improve the success of artificial insemination.